Older Adults Home-Based Care in Cairo: Asset Mapping Towards Community Development - El-Taweel, Yomna (AUC Knowledge Fountain, 2022)
The health and economic consequences of the rapid growth of the older adults’ population above 60 have led to new and more flexible forms of care, including home-based care. In Cairo, Egypt, there seems to be a high demand and preference for home-based care services over other care services like nursing homes. From a policy makers’ perspective, older adults’ needs are sometimes approached in a deficit-oriented way. This might contribute to the disempowerment of older adults and make them feel like people with needs that can only be met by external support. This mixed-method study aimed to contribute to the field’s understanding by exploring assets in the home-based care field. Thus, an Asset-Based Community Development (ABCD) approach was used as a framework. The ABCD model focuses on assets available within a community rather than weaknesses and problems. Data collection covered different perspectives of field experts, including NGOs, private companies, caregivers, and religious entities as well as other concerned stakeholders. Following a desk review, two methods of qualitative inquiry were used to identify assets. For part I, appreciative interviewing was used to analyze community successes. For part II, asset mapping was used to understand assets’ organization. For the first part, interviews were conducted, and survey data were collected with experts in the field to gain insight and broaden the perspective on existing assets. Data was analyzed using thematic analysis along with descriptive statistics. The results helped explore the home-based care field, define the available service providers and details of the offered services, and related governing framework. Results also helped understand different perspectives on home-based care and how they relate to resources available within the home-based care community. The resources and assets available within the home-based care community included skills, capabilities, volunteer associations, institutions, physical location, and connections assets. Despite the many assets and resources, participants mentioned some challenges affecting service providers or older adults, and they discussed experts’ suggestions for field improvement. As for the second part, Geographic Information System mapping (GIS) was used for data representation. Exploratory spatial analysis was applied to obtain a more specific overview of the home-based care field within certain geographical contexts, especially the relationship between the supply and demand of services. The geographic mapping of the relevant assets pointed to three districts that differed in the number of services available. Comparison analysis of the characteristics within these districts emphasized the economic and cultural impact on existing services: the highest served district (New Cairo First) is known to be a high socioeconomic neighborhood, that has a higher employment rate and a larger population with higher education; while the least served district (Ain Shams) is one of Cairo’s old districts with traditional family values, and has a lower employment rate, a smaller population of highly educated people and a larger population with intermediate education or lower. Recommendations included improving governance, building on existing collaborations, enhancing economic development, increasing volunteer organizations, and accounting for the various older adult’s needs are discussed. These recommendations are expected to contribute to the home-based care field development in urban Cairo and provide better services to older adults.